Emotional agility : get unstuck, embrace change, and thrive in work and life - David, Susan A., ....- (London : Penguin, 2017)
"The counterintuitive approach to achieving your true potential, heralded by the Harvard Business Review as a groundbreaking idea of the year. The path to fulfillment, whether at work or at home, is almost never a straight line. Ask anyone who has achieved their biggest goals or who thrives in their relationships, and you'll hear stories of many unexpected detours along the way. What separates those who rise to these challenges and those who get derailed? The answer is agility--emotional agility. Emotional agility is a four-step approach that allows us to navigate life's twists and turns with self-acceptance, clear-sightedness, and an open mind. In her more than twenty years of research, Susan David has found that no matter how intelligent, resilient, or creative people are, when they ignore how situations or interactions make them feel, they miss opportunities to gain insight, getting hooked by thoughts, emotions, and habits that prevent them from reaching their full potential. Emotionally agile people experience the same stresses and setbacks as anyone else, but they know how to adapt, aligning their actions with their values and making small changes that lead to a life of growth. Drawing on her extensive professional research, her international consulting work, and her own experiences growing up in Apartheid-era South Africa and losing her father at a young age, David shows how anyone can become more emotionally agile and thrive in an uncertain world. Written with authority, wit, and empathy, Emotional Agility will help you live your most successful life, whoever you are and whatever you face"--
"The counterintuitive approach to achieving your true potential, heralded by the Harvard Business Review as a groundbreaking idea of the year"--
Keywords: Adjustment (Psychology).; Emotions; Resilience (Personality trait).; Self-realization.